Examining Migrant Workers’ Rights in Fishing Industry of Thailand after Ratification of ILO C188: A Case Study of Burmese Migrant Workers in Ranong Province, Thailand - Zin Thin, Shwe; Siriwato, Sasiphattra (Journal of Contemporary Social Sciences and Humanities, 2025)
Thailand’s fishing industry is heavily reliant on migrant workers and has been boycotted by several members of the international community for human rights violations, leading to significant losses of seafood export value and revenue. The ratification of the ILO Work in Fishing Convention, 2007 (C188), in 2019 was a demonstrative step taken by Thailand to potentially improve the working conditions of fishers, and to assure the international community that Thai seafood products are free from labor and human rights abuses. Thailand is the only country in Southeast Asia to ratify C188, and it appears the ratification was driven by economic incentives and access to export markets. This research aims to examine the current situation of migrant workers in the Thai fishing industry post-C188 ratification, using Ranong Province as a case study. It also proposes a set of recommendations on how the situation of migrant workers in Ranong’s fishing industry can be improved. Thirteen (13) participants from government agencies, NGOs, migrant workers, and employers were interviewed. The research found that the current working conditions of fishers in Ranong’s fishing sector have not authentically met C188 standards. Notable violations include issues related to health and safety, payment structures, and employment contracts, all of which fall significantly below C188 requirements. Many fishers tend not to approach public authorities to report these violations due to fear, intimidation or lack of trust. Recommendations to help minimize C188 violations include improving reporting mechanisms at PIPO, taking immediate legal action against violators (sanctions), allowing migrant fishers to form their own union, reducing documentation and recruitment costs, and simplifying the immigration process.